Evaluating fossil charcoal representation in small peat bogs: Detailed Holocene fire records from southern Sweden. (November 2020) - Cui, Qiao-Yu; Gaillard, Marie-José; Vannière, Boris; Colombaroli, Daniele; Lemdahl, Geoffrey; Olsson, Fredrik; Benito, Blas; Zhao, Yan
In this study, we assess how representative a single charcoal record from a peat profile in small bogs (1.5–2 ha in area) is for the reconstruction of Holocene fire history. We use high-resolution macrocharcoal (>250 μm) analysis of continuous series of 2 cm 3 samples from two small bogs in southern Sweden. We compare (1) duplicate charcoal records from the same core, (2) duplicate charcoal records from profiles in the same site (10 m apart), and (3) charcoal records from two sites within the same region (15 km apart). Comparisons are made for charcoal counts and area expressed as accumulation rates. The results suggest that (a) charcoal counts and area are highly correlated in all records; (b) duplicate charcoal records within the same core are very similar, although some charcoal peaks are found in only one of the two records; (c) although long-term trends in fire regimes are similar between duplicate charcoal records from nearby profiles within the same site and between charcoal records from sites within the same region, some individual charcoal peaks/fire events are asynchronous between records. The known historical fires of the town of Växjö (1570 and 1612 CE) are recorded at the two study sites, which indicates a macrocharcoal source area of minimum 15 km in diameter. The 2 cm 3 peat samples contained relatively low amounts of macrocharcoal; we therefore recommend to analyse larger samples from small peat bogs with comparable peat accumulation rates. This will improve the reliability of the macrocharcoal record and its interpretation.